Physicochemical and Functional Properties of Bario Rice Varieties as Potential Gluten-Free Food Ingredients - Mohd Azlie, Noorul Athiera; Jailani, Fadhilah (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study aimed to analyse the proximate composition, physical characteristics, and functional attributes of flour of four selected varieties of Bario rice (Oryza sativa L. Opaceae.): Bario Adan, Bario Padan, Bario Hitam, and Bario Kulit Merah. The rice flour was prepared using a semi-wet grinding method. The results on proximate composition showed that the moisture content ranged from 12.56% to 13.87%. All flours were high in crude fibre and low in fat content ranged 23.07 to 25.30% and 2.46 to 2.69%, respectively. Bario Padan exhibited the highest amount of crude fibre and protein (p<0.05). There were significant differences (p<0.05) observed for L, a*, and b* values, Bario Hitam shows the lowest L* (5.29) and b* (4.96) value (p<0.05). The functional properties among flour variety differ significantly (p<0.05) with a range of 1.160 to 1.257 g/g for water absorption capacity and oil holding capacity ranged from 0.970 to 1.158 g/g. Highest swelling power was obtained in Bario Adan (5.594 g/g) while Bario Padan possessed highest water solubility index (0.099%). In conclusion, Bario rice varieties showcased favourable nutritional and functional traits, indicating their potential as gluten-free ingredients in the formulation of food products.